Experience of Iraqi Women Who Received In Vitro Fertilization Treatment in the Erbil Maternity Teaching Hospital, Iraq - Jamil Piro, Tiran; Hamdia; Safary, Kolsoom (International Journal of Psychosocial Rehabilitation, 2020)
Background: Women who experience in-vitro fertilization (IVF) treatment report increased levels of distress as this condition impacts virtually every aspect of their lives. This is true throughout the world, including in the Kurdistan region of Iraq. This is the first qualitative study that aims to explore and describe the experiences of Kurdish women undertaking IVF therapy in Erbil, Iraq. Methods: This qualitative study based on a thematic analysis approach targeted a sample group of women who were seeking infertility treatment through IVF at a referral center in Hawler Maternity Hospital. Semi-structured interviews were utilized to gather data. Results: Through analysis, four main categories of respondents’ attitudes were identified, including “gleam of hope along with fear,” “stabilization of marital relationship,” “attention reception,” and “social criticism.” Conclusions: The findings from this study are important for informing care by fertility specialists and healthcare workers who interact with patients at fertility clinics. Results can be used to gain a deeper understanding of Kurdish women’s feelings and emotions regarding IVF treatment from the perspective of their sociocultural values and norms.